Facile synthesis of N-benzylated 3-alkyl-2,6-diarylpiperidin-4-ones: Stereochemical investigation by 1D/2D NMR and single-crystal XRD - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2011)
A series of thirteen 1-benzyl-3-alkyl-2,6-diarylpiperidin-4-ones 14-26 were conveniently synthesized in high yields 87-92%. In order to find the impact on piperidone stereochemistry, beside the N-benzylation, methyl/ethyl/isopropyl groups at C-3 and halo/alkyl/alkoxy/benzyloxy groups on the phenyl rings at C-2/C-6 were introduced. All the synthesized compounds were characterized by mass, (1)H and (13)C NMR spectral studies. Of them, the 1-benzyl-3-ethyl-2,6-diphenylpiperidin-4-one 22 was completely characterized by 2D NMR techniques such as (1)H-(1)H COSY, (1)H-(13)C COSY and NOESY to assign the signals, unambiguously. The proton coupling constants and NOE correlations provided the complete stereochemistry of 22, which is further witnessed by its single-crystal XRD analysis. The NMR and XRD studies revealed that the compound 22 exists in a chair conformation with equatorial orientation of all the substituents in both solution and solid states. On the basis of their vicinal coupling constants, the chair conformation with equatorial orientation of the substituents at C-2, C-3, C-6 and N is proposed for all compounds 14-26; moreover, a considerable population of boat conformation also suggested for the compound 26 along with the predominant chair conformation, in solution. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2D NMR; Conformation; N-benzylation; Piperidin-4-one; single-crystal XRD; Stereochemistry

Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one

Design, synthesis and cytotoxicity of novel N-benzylpiperidin-4-one oximes on human cervical cancer cells - Dindulkar, Someshwar D.; Bhatnagar, Ira; Gawade, Rupesh L.; Puranik, Vedavati G.; Kim, Se-Kwon; Anh, Dong Hyun; Parthiban, Paramasivam; Jeong, Yeon Tae (Journal of Chemical Sciences, 2014)
A series of fifteen diversified N-benzylpiperidin-4-one oximes were synthesized and characterized by their NMR spectral data. Additionally, single-crystal XRD analysis was performed for the representative symmetrically and unsymmetrically substituted molecules. All the synthesized oximes from unsymmetrical ketones existed as E-isomer as witnessed by their NMR and XRD data. Among the synthesized target compounds that evaluated for their in vitro cytotoxicity against human cervical carcinoma (HeLa) cells, five compounds were potent with IC50 < 17 mu M. 1-Benzyl-2,6-bis(4-isopropylphenyl)-3-methylpiperidin-4-one oxime 3c with an IC50 of 13.88 mu M was found to be the best active compound as depicted by the microscopic analysis.
Keywords: Cytotoxicity; HeLa cells; N-benzylpiperidin-4-one oximes; single-crystal XRD